Open science for the ocean. Recommendations from the perspective of marine carbon observations in Germany, Brazil, and beyond - Mirja Schoderer; Henry Bittig; Karel Castro Morales; Leticia Cotrim da Cunha; Claas Faber; Ramona Hägele; Birgit Klein; Arne Körtzinger; Carlos Musetti; Raquel Oliveira; Tobias Steinhoff; Cathy Wimart-Rousseau; et al. (Marine Policy, 2025)

Assessing seasonal and interannual changes in carbonate chemistry across two time-series sites in the North Western Mediterranean Sea - Cathy Wimart-Rousseau; Thibaut Wagener; Anthony Bosse; Patrick Raimbault; Laurent Coppola; Marine Fourrier; Caroline Ulses; Dominique Lefèvre (Frontiers in Marine Science, 2023)
Sustained time-series measurements are crucial to understand changes in oceanic carbonate chemistry. In the North Western Mediterranean Sea, the temporal evolution of the carbonate system is here investigated based on two 10-year time-series (between January 2010 and December 2019) of monthly carbonate parameters measurements at two sampling sites in the Ligurian Sea (ANTARES and DYFAMED). At seasonal timescale, the seawater partial pressure of CO 2 ( p CO 2 ) within the mixed layer is mostly driven by temperature at both sites, and biological processes as stated by the observed relationships between total inorganic carbon ( C T ), nitrate and temperature. This study suggests also that mixing and water masses advection could play a role in modulating the C T content. At decadal timescale, significant changes in ocean chemistry are observed with increasing trends in C T (+3.2 ± 0.9 µmol.kg −1 .a −1 – ANTARES; +1.6 ± 0.8 µmol.kg −1 .a −1 – DYFAMED), associated with increasing p CO 2 trends and decreasing trends in pH. The magnitude of the increasing trend in C T at DYFAMED is consistent with the increase in atmospheric p CO 2 and the anthropogenic carbon transport of water originating from the Atlantic Ocean, while the higher trends observed at the ANTARES site could be related to the hydrological variability induced by the variability of the Northern Current.

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.